STANDAR PENGELOLAAN DALAM MEWUJUDKAN SEKOLAH YANG EFEKTIF - Sulaeman Sulaeman; Gatot Handoko; Aep Saepudin; Ujang Cepi Barlian (Lembaga Publikasi Ilmiah, 2022)
Education management standards are one of the first instruments that are expected to be used to determine and assess the level of effectiveness and success of education management in school institutions. The results of the assessment can then be used as points that must be used as a reference for making efforts towards a superior school. Excellent schools are schools that have an effective, transparent and accountable management system, and are able to empower every important component of the school, namely educators, education staff, and all stakeholders both internally and externally, in order to achieve the school's vision, mission, and goals effectively. and efficient. The concept of effective school management is school management that is able to optimize all positive inputs and the process of realizing the vision, mission, and goals for the achievement of educational output, namely the achievement of qualified students, especially those that can be measured by the achievement of students' abilities in terms of learning competencies Effective school characteristics Among them are: 1) Leadership of qualified principals 2) Setting high standards for student achievement 3) Orientation to basic competencies 4) Maintaining a learning culture atmosphere. Principal leadership is very important to be able to realize the effectiveness of school management, because the principal is the (key person) or the key to success in realizing the vision, mission, and goals of superior schools that are effective in their management. ABSTRAK Standar Pengelolaan pendidikan merupakan salah satu instrumen pertama yang diharapkan dapat digunakan untuk mengetahui dan menilai tingkat efektifitas dan keberhasilan pengelolaan pendidikan di lembaga sekolah. Hasil dari penilaian tersebut selanjutnya dapat dijadikan poin-poin yang harus dijadikan acuan untuk melakukan upaya menuju sekolah unggul. Sekolah unggul yaitu sekolah yang memiliki sistem pengelolaan yang efektif, transparan dan akuntabel, serta mampu memberdayakan setiap komponen penting sekolah, yaitu pendidik, tenaga kependidikan, dan semua stakeholder baik secara internal maupun eksternal, dalam rangka pencapaian visi, misi, dan tujuan sekolah secara efektif dan efesien. Konsep pengelolaan sekolah efektif adalah pengelolaan sekolah yang mampu mengoptimalkan semua masukan positif dan proses realisasi visi, misi, dan tujuan bagi ketercapaian output pendidikan, yaitu prestasi anak didik yang mumpuni terutama yang bisa diukur dengan tercapainya kemampuan anak didik dalam hal kompetensi belajar Karekteristik sekolah yang efektif diantaranya adalah: 1) Leadership kepala sekolah yang mumpuni 2) Membuat Standar yang tinggi terhadap prestasi anak didik 3) Berorientasi terhadap kompotensi dasar 4) Menjaga atmosfir budaya belajar. Leadership kepala sekolah sangat penting untuk bisa mewujudkan efektifitas pengelolaan sekolah, karena Kepala sekolah merupakan (key person) atau kunci sukses dalam mewujudkan visi, misi, dan tujuan sekolah unggul yang efektif dalam pengelolaanya.